Using micro-indentation to determine the elastic modulus of shale laminae and its implication: Cross-scale correlation of elastic modulus of mineral and rock. (September 2022) - Li, Lihui; Huang, Beixiu; Tan, Yufang; Li, Xiao; Ranjith, P.G.
Abstract: Lamina is the smallest megascopic layer in a sedimentary sequence. Different laminae are usually distinguished by various mineral compositions and different thicknesses ranging from tens of micrometers to several millimeters, which significantly affects shale deformation and fracture extension during shale gas/oil exploitation. Nevertheless, due to the minute thickness of laminae, it is hardly possible to determine their elastic moduli by traditional standard mechanical methods and detailed mechanical properties of laminae have been rarely reported. In this work, we studied the elastic modulus differences of laminae in continental shale using micro-indentation technique and scanned electronic microscope (SEM) equipped with automatic mineral identification and characterization system (AMICS). The results demonstrate that the elastic moduli of laminae are highly heterogeneous and can be classified into three types: the stiffer layer, the intermediate layer, and the soft layer, corresponding to the pyritic lamina, the sandy lamina, and the organic-rich lamina, respectively. Additionally, the elastic modulus of lamina excellently correlates with mineral compositions, with the weight coefficients of different minerals on the composite elastic modulus of lamina differing greatly. With the combination of the thickness and the elastic modulus of every single lamina within the shale, it is accessible to obtain the elastic modulus of shale by analytical solutions. Therefore, an efficient method is proposed to characterize the cross-scale elastic modulus from nano/submicron mineral to macro rock based on the mineral components and geometric analysis of laminae, which is rapid and economically feasible, particularly helpful when neither sufficient samples nor logging data are available. Highlights: Conducting micro-indentation tests and mineral identification on various laminae. Laminae in continental shale are heterogeneous in elastic moduli. Elastic moduli of shale laminae are strongly composition-dependent. Establishing the relationship of elastic modulus cross-scale from mineral to rock.